The Relationship between Suicidal Tendencies and Psychological Pressures and Certain Demographic Variables for a Sample of Secondary School Students and University Students in Riyadh City - Alghamdi, Mohammed Qaed Zaid (Journal of Educational and Psychological Sciences, 2020)
This study aims to identify the relationship between suicidal tendencies and psychological pressures for a sample of secondary school students and university students in Riyadh city. It also aims to reveal the differences in the suicidal tendencies level and psychological pressures in light of the following variables (education stage - parents' educational level - family's economic level).This research is applied to a sample of (100) secondary school students and (100) university students in Riyadh city.The researcher applied the following scales to the study sample members: suicidal tendencies scale prepared by Alshehri, Mohammed (2010), psychological pressures scale prepared by Alshawi, Suliman (2010) regulated to Saudi environment.The study findings revealed that there was a statistically significant positive correlation between psychological pressures and suicidal tendencies; there were statistically significant differences between the average score of secondary school students and university students in terms of suicidal tendencies in favor of the university students; there was a statistically significant negative correlation between the level of household's income and suicidal tendencies; there was a statistically negative correlation between father's educational level and suicidal tendencies; there was a statistically negative correlation between mother's educational level and suicidal tendencies.The research concluded a combination of recommendations that reduce the psychological pressures and suicidal tendencies for secondary school and university students. It also recommended researching the factors that increase the psychological pressures and suicidal tendencies for secondary school and university students. It also suggested providing proper solutions to create a suitable environment that reduces the psychological pressures and suicidal tendencies for secondary school and university students.
Keywords: Suicidal Tendencies; Psychological Pressure; secondary School Students; University Students